TRANSFORMING DISCOURSE INTO PRACTICE: COMPUTERHYSTORIES AND DIGITAL CULTURES AROUND 1984. - Harrasser, Karin (Cultural Studies, 2002)
This paper discusses some theoretical approaches to the question of how culture, technologies and the social interact. These considerations result from the author's research in the genesis of digital cultures in the 1980s. The paper begins by outlining the author's research project, and then continues with a discussion of some of the most influential approaches in the cultural studies of technology.This article then presents a small sample of the author's analysis, which combines narratological and discourse analytical methods with practice-oriented cultural theories, such as those of Pierre Bourdieu, Régis Debray and Bruno Latour.